Brain gangliosides in axon-myelin stability and axon regeneration - Schnaar, Ronald L. (2009)
Gangliosides, sialic acid-bearing glycosphingolipids, are expressed at high abundance and complexity in the brain. Altered ganglioside expression results in neural disorders, including seizures and axon degeneration. Brain gangliosides function, in part, by interacting with a ganglioside-binding lectin, myelin-associated glycoprotein (MAG). MAG, on the innermost wrap of the myelin sheath, binds to gangliosides GD1a and GT1b on axons. MAG-ganglioside binding ensures optimal axon-myelin cell-cell interactions, enhances long term axon-myelin stability and inhibits axon outgrowth after injury. Knowledge of the molecular interactions of brain gangliosides may improve understanding of axon-myelin stability and provide opportunities to enhance recovery after nerve injury.